Features of the transformation of the self-concept of a woman - Danyliuk, Ivan; Klimash, Tamara (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
B a c k g r o u n d . The self-concept of a person is a phenomenon that includes a person's ideas about himself and his own assessment of these ideas. Representatives of various directions in psychology emphasized that a positive self-concept of an individual is a condition for a fully functioning and prosperous individual who is fully aware of his self, knows and knows how to use his advantages and disadvantages, and strives to realize his potential (K. Rogers, R. Burns, J. Nezlek, R. Plesko, etc.). R. Burns was the first to propose the division of self-concept orientation into positive and negative. Dichotomous influence on the self-concept of an individual is carried out constantly and manifests itself in various life situations. Positive transformations of the self-concept occur under the influence of various factors, in particular, they are provoked by personal traits – benevolence, conscientiousness, neuroticism, etc. (J. Campbell, I. Tokunaga, T. Horiuchi, etc.).M e t h o d s . The following methods were used to investigate the characteristics of the transformation of the self-concept of a person: Self- actualization test SAMOAL (to study a person's attitude towards himself/herself and the desire for self-actualization), R. Kettel's 16-factor personality questionnaire (16РF) (to study personal characteristics), tolerance scale to the uncertainty of S. Badner (to study the attitude towards oneself and to changes), H. Ammon's self-structural test (to clarify the central structures of the self); projective technique "Ideal Self" (to study the cognitive component of self-concept); the projective technique "Cube in the desert" (for researching the level of comfort in current life conditions and features of the social orientation of the individual).R e s u l t s . Constructive transformation is evidenced by the presence of adequate positive self-esteem, active construction of one's own life, activity, desire to realize oneself, carefreeness, high work capacity, frankness, absence of social stereotypes, energy, satisfaction with work experience in one's specialty, ability to act adequately in relation to threatening circumstances, ability to enjoy sexual contacts , the ability to understand the feelings and interests of others, reluctance to recognize authority and pressure from others, independence, the desire for a harmonious existence and healthy relationships with other people, straightforwardness, psychological maturity, relaxation, courage, restraint, a tendency to think independently, a creative attitude to one's own life , patience, tolerance for uncertainty. A negative transformation of the self- concept is evidenced by the presence of activity, great fear of death and loneliness, high work capacity, rejection of one's own interests and needs, lack of trust in authoritative people, lack of contact with oneself, a flexible approach to one's own unconscious and feelings, emotional stability, intolerance to uncertainty, ease in relationships, independence, inability to live in the present, inability to accept criticism, unrealistic self-esteem, straightforwardness, depression, decisiveness, following generally accepted norms, courage, social hyperadaptability, tendency to benevolent social contacts, tolerance for criticism.С o n c l u s i o n . Features of the transformation of the self-concept of women aged 26 to 40 are presented. The transformation of the self- concept of an individual takes place in two directions. Constructive transformation contributes to the formation of a positive self-concept, destructive transformation – a negative self-concept. The subjective assessment of personal realization is an indicator of the orientation of the transformation of self-concept: a person with a formed positive self-concept is sure that it is realized in life; a person with a negative self-concept indicates that he is unfulfilled and has serious difficulties with self-actualization.
Keywords: self-concept of the individual; dichotomous orientation of the transformation of the self-concept of the individual; constructive transformation of the self-concept of the individual; destructive transformation of the self-concept of the individual